2005
DOI: 10.1016/j.ceca.2004.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid turnover of the “functional” Na+–Ca2+ exchanger in cardiac myocytes revealed by an antisense oligodeoxynucleotide approach

Abstract: Antisense oligodeoxynucleotides (AS-ODNs) were used in combination with transient functional expression of the cardiac Na(+)-Ca2+ exchanger (NCX1) to correlate suppression of the Na(+)-Ca2+ exchange function with down-regulation of NCX1 protein expression. In a de-novo expression system (Sf9 cells), a decrease in both, NCX1 mRNA and protein after AS-ODN application was paralleled by diminished NCX1 activity, a typical hallmark of a true "antisense effect". Although AS-ODN uptake was also efficient in rat neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…NCX1 has high affinity interactions with ankyrin (Li et al 1993; Mohler et al 2005), and in cell lines both the activity and localization of NCX1 appear to depend on actin cytoskeleton (Condrescu & Reeves, 2006). Na + –Ca 2+ exchangers have recently been suggested to move in and out of the cardiac surface membrane more frequently than expected from total protein half‐life (Egger et al 2005). The exchanger has a putative endocytosis motif (YCH) close to its C‐terminus (Linck et al 1998), and it is suggested to interact with caveolins that may take part in clathrin‐independent membrane trafficking (Bossuyt et al 2002).…”
mentioning
confidence: 99%
“…NCX1 has high affinity interactions with ankyrin (Li et al 1993; Mohler et al 2005), and in cell lines both the activity and localization of NCX1 appear to depend on actin cytoskeleton (Condrescu & Reeves, 2006). Na + –Ca 2+ exchangers have recently been suggested to move in and out of the cardiac surface membrane more frequently than expected from total protein half‐life (Egger et al 2005). The exchanger has a putative endocytosis motif (YCH) close to its C‐terminus (Linck et al 1998), and it is suggested to interact with caveolins that may take part in clathrin‐independent membrane trafficking (Bossuyt et al 2002).…”
mentioning
confidence: 99%
“…Similarly, the turnover rate of the NCX measured using metabolic labeling in lysates from neonatal cardiomyocytes yields a long half-life of 33 hours [64]. Whereas the functional half-life of NCX in the plasma membrane as indicated by channel activity is likely to be much faster at under 12 hours [65, 66], indicating regulation by channel binding partners at the local environment. The importance of protein-protein interaction on channel half-life is further supported by the fact that coexpression of Kv1.3 with their regulators in neurons significantly changes its half-life at the plasma membrane [67].…”
Section: Cardiac T-tubulesmentioning
confidence: 99%
“…For example, Connexin 43 (Cx43) gap junction proteins have a half-life of 1–3 hours 1, 2 while potassium channels, calcium channels, and the sodium-calcium exchanger have half-lives that are reported in the 2–8 hours range 36 . The short life span of ion channels suggests there needs to be efficiency in their life-cycle and movements which follow the order of: formation, delivery to the correct subdomain on plasma membrane, behavior once in membrane, and internalization back into the cell.…”
Section: Overview Of Ion Channel Trafficking In the Heartmentioning
confidence: 99%